Experimental evidence quantifying effects of nocturnal light conditions on predation levels by riverine predators on larval prey - Joseph J. Riedy; Edward A. Baker; Kim T. Scribner (Journal of Freshwater Ecology)
Larval fish and aquatic macroinvertebrates are believed to be at greater predation risk by visual riverine predators during periods of higher lunar illumination. Predation rates may also be affected by the taxonomic composition and relative abundance of alternative co-distributed prey. We experimentally tested whether differences in larval lake sturgeon (Acipenser fulvescens) predation levels were attributed to changes in prey selectivity, or to an overall decrease in consumption of co-distributed and dispersing prey consumed by predatory riverine species under different light conditions. Larvae from three common riverine prey taxa observed nocturnally dispersing together (lake sturgeon, white suckers (Catostomus commersonii), and Hetptageniid mayflies) were released concurrently into raceway mesocosms. Raceways contained one of two abundant predacious riverine fishes [either rock bass (Ambloplites rupestris) or hornyhead chub (Nocomis biguttatus)]. Trials were conducted in light conditions simulating a full or new moon. Both predators consumed fewer prey under new moon relative to full moon light conditions. In full moon conditions, rock bass selected for mayflies and against white suckers, but in new moon conditions rock bass selectivity was similar for all prey. Hornyhead chub selected for mayflies under both light conditions. Results indicate rock bass and hornyhead chub rely on visual cues to detect prey. Rock bass also appeared to visually differentiate between prey taxa, whereas hornyhead chub may use alternative senses to select prey. Variation in larval lake sturgeon mortality during the downstream drifting period was a function of the taxonomic composition and size distribution of predators, and composition and relative abundance of alternative co-distributed prey. Nocturnal light levels likely also influence predation rates in natural populations of nocturnally dispersing aquatic larvae. Light levels during larval dispersal should be considered when interpreting intra- and inter-annual variation in recruitment in species of regional conservation concern.